STRATEGI KEPEMIMPINAN DALAM PENDIDIKAN - Baharuddin (Almeera Education, 2022)
The purpose of this article is to provide a general view of the concept of leadership from several aspects, namely psychology, management and education through presenting various ideas and interpretations, although not final conclusions. The main discussion in this article: